Produksi Darah Dan Karakteristik Pendonor Darah Berdasarkan Golongan Darah ABO Dan Rhesus Di UTD PMI Kota Yogyakarta Tahun 2019 - Putri, Arum Sari Dwi; Supadmi, Francisca Romana Sri; Mumpuni, Nurpuji (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Blood type is a unique characteristic of blood in individuals because of the different kinds of carbohydrates and proteins on the surface of red blood cell membranes which classified into blood type A, B, O, and AB. In addition to proteins A and B, there is a factor of rhesus blood type that is positive and negative. Suitability of blood types are very crucial when used for blood transfusion purposes. Proper grouping of blood groups can minimize the risk of transfusion reactions to recipients. This research identifies the blood production and characteristics of blood donor based on the ABO blood group and Rhesus, gender, age, and donor type in the Blood Transfusion Service of Yogyakarta’s Indonesian Red Cross in 2019. The design of research is descriptive retrospective. The result of this study is the majority of blood groups production is O Rh+ 17.165 (37,23%) and O Rh- 47 (0,10%), while the fewest is AB Rh+ 3.567 (7,73%) and AB Rh- 1 (0,00%). The result of this study is the majority of blood groups production is O Rh+ 17.165 (37,23%) and O Rh- 47 (0,10%), while the fewest is AB Rh+ 3.567 (7,73%) and AB Rh- 1 (0,00%). The majority of the blood donor’s gender is male 35.721 (77,47%), for female 10.388 (22,53%). The majority of the blood donor’s age is 18-24 years old 13.335 (28,92 %); the fewest is 17 years old 317 (0,69%). The majority of the type of donor is routine voluntary blood donors 33.602 (72,88%) and new voluntary blood donors 12.507 (27,12%) from 46.109 blood donors.